Changes in Anterior Segment Morphology and Intraocular Pressure after Cataract Surgery in Non-glaucomatous Eyes - Giglio, Rosa; Inferrera, Leandro; De Giacinto, Chiara; DʼAloisio, Rossella; Beccastrini, Andrea; Vinciguerra, Alex Lucia; Perrotta, Alberto Armando; Toro, Mario Damiano; Zweifel, Sandrine; Tognetto, Daniele (Klinische Monatsblätter für Augenheilkunde, 2023)
Background It is known that cataract extraction is associated with a significant reduction in intraocular pressure, especially in narrow angled eyes; however, the modifications of anterior segment parameters associated with this phenomenon have still not been completely defined. The purpose of this study was to evaluate changes in anterior segment anatomy and intraocular pressure after cataract surgery in non-glaucomatous eyes.Methods and Material This retrospective case series study included 64 eyes of 64 consecutive patients who underwent phacoemulsification with intraocular lens implantation. Anterior segment parameters and intraocular pressure were assessed and compared before and 6 months after surgery. Anterior segment imaging was performed using Casia SS-1000 anterior segment optical coherence tomography (Tomey, Nagoya, Japan). Anterior segment measurements included anterior chamber depth, anterior chamber width, anterior chamber volume, angle opening distance at 500 µm anterior to the scleral spur, angle recess area 750 µm from the scleral spur, lens vault, trabecular iris space area at 500 µm from the scleral spur, and trabecular iris angle at 500 µm from the scleral spur. Intraocular pressure was measured using the Goldmann applanation tonometer (Model AT 900 C/M, Haag-Streit, Bern, Switzerland). Anterior segment parameters and the relationship of changes in intraocular pressure were also evaluated.Results All anterior segment parameters increased significantly after surgery (p < 0.05). Both angle opening distance at 500 µm anterior to the scleral spur and anterior chamber depth changes were positively correlated with the preoperative lens vault. The mean intraocular pressure significantly decreased from 14.91 mmHg (± 2.8 SD) to 12.91 mmHg (± 3.13 SD) (p < 0.001). Changes in intraocular pressure correlated negatively with values for the width of the preoperative anterior chamber (r = − 0.533; p = 0.001).Conclusion Cataract surgery led to significant widening of the anterior chamber angle and lowering of intraocular pressure. Further investigations are needed to better understand whether anterior chamber width may be a new independent predictive factor for reduction in postoperative intraocular pressure.
Keywords: intraocular pressure; cataract surgery; anterior segment OCT; anterior segment morphology